Communist censorship in Hungary and beyond - Gombár, Zsófia (2025)
This chapter provides a comprehensive overview of the history of censorship in Hungary with the main focus on literary translations made under Communist rule. Literary publications were primarily filtered through pre-selection restraint exercised by publishing professionals whose work was monitored by a varying set of censoring institutions. Although self-censorship was a central element in the constraining mechanism of the Rákosi era as well, it became the dominant form of control under the Kádár administration. The study collects all currently available evidence on the existence of censorship in State-Socialist Hungary and makes suggestions for further study.